The Impact of Digital Marketing: A Systematic Literature Review - Qurtubi; Melinska Ayu Febrianti; Muchamad Sugarindra; Anas Hidayat; M Suyanto (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The development of internet influences business, operationally and strategically. People has reached wider connection towards information. This leads to several marketing transformations, from conventional to digital technology conducted by businessmen. Yet, several marketing managers still unsure in such communications through digital channel and its impacts. This research is purposed to analyse the strategy and the content of the implementation of digital marketing, and to provide opportunity for future research. This research applies systematic literature review method towards 45 literatures. Later, it could be resumed the impacts that influence the company internally or externally in terms of global perspective, the frequent-used elements or contents in digital marketing strategies as well as the opportunity for future research to obtain comprehensive and accurate result for businessperson.